Beban Dan Koping Caregiver Dalam Merawat Klien Gangguan Jiwa Di Kecamatan Pahandut Kota Palangka Raya - Missesa Missesa (JURNAL KEPERAWATAN MERSI, 2020)
Background: Insident mental disorder 0.9 permill and emotional disorders 3.2 % on Province of Central Kalimantan.  Based on this population, the estimated number of mental disorders in Central Kalimantan at productive age is around 1,360 people experiencing serious mental disorders. The caregiver is the patient's closest person who has the burden of responsibility as long as the patient is treated at home, the caregiver is generally a family memberMetode: To gain an in-depth understanding of caregiver burden and coping, the condition of mental patients and load management in caring for mental patients. The benefit of this research is that this research is expected to provide an overview of the phenomenon of caring for mental disorders at home which is a reference for nurses to provide comprehensive nursing care to mental patients and caregivers. This study uses a qualitative research method of phenomenological studies. The sample in this study were caregivers who care for mental disorders clients in Pahandut District, Palangka Raya City. Data collection strategies are interviews, observation and field notes. This study pays attention to ethical principles during the research.Result: 6 (six) themes about caregiver burden and coping in caring for mental disorder clients, namely 1) Caregiver's perception of mental disorders 2) Reasons for caregivers, 3) Caregiver burden in caring for clients, 4) Caregiver coping to overcome the burden of caring for clients with disorders mental, 5) Source of caregiver support in caring for clients with mental disorders, and 6) Health care for clients is affordable and efficient.Conclusion: The nurse provides physical and psychological support to the family as the caregiver for the client with mental disorders.